Hubungan IMD, Pemberian ASI, Dan Mobilisasi Dini Dengan Penurunan TFU Hari Ke-7: The Relationship Between IMD, Breastfeeding, and Early Mobilization with Decreased TFU Day 7 - Oktavia, Gita (Dohara POAJ, 2023)
Introduction: Uterine involution is the process of the uterus returning to its pre-pregnancy state, starting after the placenta is born and lasting for about 6 weeks. The process of uterine involution is accompanied by a decrease in the height of the uterine fundus (TFU). To find out the process of uterine involution by doing a palpation examination to feel where the TFU is. Many factors can affect the process of reducing TFU, including IMD, breastfeeding, and early mobilization. This study aims to determine the relationship between IMD, breastfeeding, and early mobilization with a decrease in TFU on the 7th day at PMB Midwife Sumiati, Palasari Village, Cipanas District, Cianjur Regency in 2022. Methods: This type of research is quantitative research in the form of correlation research with a cross-sectional design approach. The research sample is 35 respondents, with the sampling technique that is the total sampling technique. The statistical test used in this study is the Chi-square test. Results: Based on the results of the study, it was found that there was a significant relationship between the implementation of IMD (p-value = 0,032 ≤ 0,05); breastfeeding (p-value = 0,002 ≤ 0,05); and the implementation of early mobilization (p-value = 0,011 ≤ 0,05) with a decrease in TFU on the 7th day. Discussion: The conclusion is that there is a relationship between IMD, breastfeeding, and early mobilization with a decrease in TFU on the 7th day at PMB Midwife Sumiati, Palasari Village, Cipanas District, Cianjur Regency in 2022. Suggestions for postpartum mothers to carry out IMD, early mobilization, and breastfeed their babies exclusively so that mothers may experience uterine involution process that is progressing normally or accordingly.